2020
DOI: 10.1111/jnc.15233
|View full text |Cite
|
Sign up to set email alerts
|

Targeting transthyretin ‐ Mechanism‐based treatment approaches and future perspectives in hereditary amyloidosis

Abstract: The liver‐derived, circulating transport protein transthyretin (TTR) is the cause of systemic hereditary (ATTRv) and wild‐type (ATTRwt) amyloidosis. TTR stabilization and knockdown are approved therapies to mitigate the otherwise lethal disease course. To date, the variety in phenotypic penetrance is not fully understood. This systematic review summarizes the current literature on TTR pathophysiology with its therapeutic implications. Tetramer dissociation is the rate‐limiting step of amyloidogenesis. Besides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 158 publications
(176 reference statements)
0
17
0
3
Order By: Relevance
“…For CMT1A, represented by six patients in this cohort, the novel substance PXT003 containing a fixed combination of baclofen, naltrexone, and sorbitol has already undergone a phase three clinical trial with promising results [5], and the decision on approval is currently pending. With patisiran and inotersen, two new substances for the treatment of ATTRv amyloidosis have been approved in 2018 as another example of recent developments in pathophysiology-based treatment in hereditary neuropathies [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For CMT1A, represented by six patients in this cohort, the novel substance PXT003 containing a fixed combination of baclofen, naltrexone, and sorbitol has already undergone a phase three clinical trial with promising results [5], and the decision on approval is currently pending. With patisiran and inotersen, two new substances for the treatment of ATTRv amyloidosis have been approved in 2018 as another example of recent developments in pathophysiology-based treatment in hereditary neuropathies [6].…”
Section: Discussionmentioning
confidence: 99%
“…As such, both entities belong to the group of rare diseases and therefore remain challenging to diagnose [4]. With new upcoming treatment approaches for both hereditary [5,6] and inflammatory [7][8][9][10] neuropathies, it becomes more and more important to recognize underlying causes and monitor treatment response [1,11]. Currently, the standard diagnostics comprise a detailed neurological examination and nerve conduction studies (NCS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both the phase 3 trial, and the long-term safety and efficacy evaluation have shown that Patisiran is an effective treatment for FAP [ 124 , 125 ]. Another drug, Inotersen is a 2′-o-(2-methoxyethyl) (2′-MOE)-modified antisense oligonucleotide can also silence the TTR gene to treat the hereditary transthyretin amyloidosis [ 126 ]. Recently, a newly designed in vivo CRISPR-Cas9-based gene-editing therapeutic agent, NTLA-2001 was introduced.…”
Section: Rna Therapies To Treat Single-gene Neurological Disordersmentioning
confidence: 99%
“…While the genetic cause of ATTRv amyloidosis itself is well understood and even targetable by several treatment options, important aspects like differences in organ tropism and manifestation onset are not well understood to date. As potential modifiers, influencing factors in the extracellular matrix, in the TTR gene itself or in other genes like RBP4 [ 5 ] have been discussed in the literature (for review see [ 6 ]). It further seems to play a role whether a patient or the affected antecedent is male or female, suggesting that X-linked genes like AR affect TTR amyloidogenesis as well [ 7 ].…”
Section: Introductionmentioning
confidence: 99%